Domingo Sánchez y Sánchez (1860–1947): Cajal’s man on the nervous system of invertebrates - Serrano-Herrera, Adela; Espinosa-Sanchez, Juan Manuel (Frontiers in Neuroanatomy, 2024)
Domingo Sánchez y Sánchez , a distinguished disciple of Santiago Ramón y Cajal, played a fundamental role in the Spanish School of Neurohistology through the meticulous use of diverse staining and microscopic techniques in the study of the histology and physiology of the invertebrate nervous system, generating valuable contributions that were recognized and cited by the scientific community. His research covered a wide range of areas: he was initially an anthropologist and zoologist, later earning a doctorate in Medicine and specializing in the neurohistology of invertebrates, including the detailed study of the retina and nerve centers of insects, and the discovery of histolysis in nerve centers of insect larvae during metamorphosis, challenging scientific paradigms of the time. Furthermore, Sánchez's work on the neurofibrils of insects was crucial in supporting Cajal's neuronal theory and refuting Bethe and Apathy's reticularist hypothesis. Additionally, he also made preliminary observations of the Golgi apparatus, the lysosomal system, the endoplasmic reticulum, and the sarcoplasmic reticulum of skeletal muscles (Cajal-Fusari network). Domingo This is a provisional file, not the final typeset article Sánchez y Sánchez's exceptional scientific research and contributions to neurohistology in 20th century Spain continue to serve as a significant legacy.